Optimalisasi Pelaksanaan Abandon Ship Drill untuk Meningkatkan Kecakapan para Kru Kapal ketika Terjadi Situasi Darurat - Dimas Surya Wicaksono; Ngurah Ade Dwi Putra Yuda; Jaka Septian Kustanto; Fazri Hermanto (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2026)
Safety of life at sea is a crucial aspect in merchant vessel operations, making crew readiness in facing emergency situations extremely important. One effort to improve this readiness is through the implementation of abandon ship drills. However, in practice, drill implementation is often not fully effective in developing crew competence. This study aims to analyze crew readiness in conducting abandon ship drills and evaluate the extent to which drill implementation has been optimal in enhancing crew competence when facing emergency situations on MV. CNC TIGER. This research uses a descriptive qualitative method with data collection techniques including direct observation, interviews with the chief officer and third officer, and documentation studies. The data obtained were analyzed using gap analysis by comparing the practice of abandon ship drill implementation on MV. CNC TIGER with international regulations SOLAS 1974 Chapter III Regulation 19. The results showed that crew readiness in conducting abandon ship drills falls into the adequate category but is not yet optimal. Although drill frequency has met SOLAS requirements, crew response to emergency alarms remains slow, understanding of duties according to the muster list has not been fully mastered, and lifeboat launching has not been carried out according to established standards. Additionally, drill implementation tends to be administrative and lacks realism, thus failing to maximize crew competence development. Therefore, optimization of abandon ship drill implementation is needed through improved training quality, scenario realism, officer leadership, and continuous evaluation to enhance crew readiness and safety.